Compute and Define Region of Elastic Reaction Force for Calculating the Section Force of Underground Construction by Finite Element Method - Nguyen , Quốc Tuyến; Le , Văn Nam (Journal of Technical Education Science, 2008)
Defining the region which effected by the elastic reaction force of underground construction had the important meaning for the calculation of underground structure’s section force. The effective of elastic reaction force plays an important role to make stability and slight the working of underground structure, control their deformation, increase the value of axial force and decrease the bending moment of structure. By the previous experiment calculation, the angle which defines the region had not effected by the elastic reaction force of ground foundation. In this paper, to define exactly the j0 angle, the region of elastic reaction force of underground structure, we used the Finite Element Method which is combined with the iterative algorithm calculation to compute section force value of the underground structure.